Modified Toca Colour Finder (M-TCF) Dan Kromatofor Sebagai Penduga Tingkat Kecerahan Warna Ikan Komet (Carasius Auratus Auratus) Yang Diberi Pakan Dengan Proporsi Tepung Kepala Udang (TKU) Yang Berbeda - Septa Indarti; Moh. Muhaemin; Siti Hudaidah (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2012)
Goldfish is one of the ornamental freshwater fish which has interesting body colour. Efforts to increase the quality of colour needs to be done, by given the material which can increasing brightness of colour infeed. One of alternative to replace such materials is the shrimp head meal (SHM). The aim of this research was determined the relationship between increased colour intensity measured  by using the Modified Toca Colour Finder (M-TCF) and the number of chromatophore cells in the epidermal layer of goldfish due to the addition of SHM in artificial feed. The research was conducted in Completed Randomize Design with the additional of SHM (0; 10; 12%) were given to 30 goldfish/aquaria for 45 days of cultured. The result showed that shrimp head meal gave significant difference by increasing colour intensity and the amount of chromatophore cells. Nevertheless the treatment did not give significant difference on  growth. There was a positive correlation between the numbers of chromatophore cells with the colour intensity of goldfish. Optimum absorb of carotenoids occured in10% added of shrimp head meal.